(3JGQjN GdVYjas - (3GdeQGHW , eMeO Hf eMeO Hf YHO GdYRjR GdeQGHW GdSLdeGSj, CHh YHO Gddg,J (B1140 (3g` s ((3eMeO Hf OGhO GdQHGWj s)
(3ChdgG (B:s
(3GHf GdMSf Hf YHOGddg Hf CHj eMeO Hf YQaI s
(3BNQgG (B:s
(3GdedjhOi hfRd HGdefRg MJi CLJeYJ Ydjg GdNjd, hai jhe GdKdGKGA GdJGSY YTQ ef UaQ GdNjQ hQO Ydi GdQHGW hdO GdYhO GdPZai eY s
(3PcQ ajg JGQjN GdOhdI GdYdhjI hMhGOKgG ef dOf EfTGFgG Edi MhGOK YGe (B1233(3g` ChGNQ CjGe GdSdWGf Gdehdi SdjeGfs
(3hdYdg Jhai aj gPg GdaJQIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B234s
Keywords: (3GdJGQjNs